Examining technical efficiency, prospects, and policies of farmers: data from a developing nation’s pineapple production - Datta, Tumpa; Saha, Jiban Krishna; Rahman, Mohammad Ataur; Adnan, K. M. Mehedi; Akter, Khadija; Chowdhury, Abhijit; Alamgir, Md. Shah (Frontiers in Sustainable Food Systems, 2024)
Introduction The unique characteristics of pineapples as a perennial plant, which guarantee their quick proliferation and adoption in both the tropics and subtropics, readily justify their economic significance. Although pineapple is a popular tropical fruit among Bangladeshi citizens, they continue to produce fewer pineapples than other international producers with limited export offerings. Hence, the study aimed to estimate the technological efficiency, prospects, and policies of pineapple growers in the northeastern district of Bangladesh. Methods One hundred respondent growers were surveyed directly to gather cross-sectional data using a multistage sampling technique. The technical efficiency scores of individual farms were calculated using the stochastic frontier model with the technical inefficiency model for identifying factors responsible for inefficiency. Results The technical efficiency scores range from about two-thirds to the absolute efficiency level, with a mean technical efficiency above the ninety percent level. The technical inefficiency effect model interpreted that farmers’ age and education had a significant positive impact, whereas credit, training, and family size had a significant negative impact on inefficiency. Discussion Findings indicated that sampled farmers may use inputs more efficiently and raise their yield by nearly one-twentieth. Therefore, the study suggests that the government should concentrate on strategies to attract young growers, as they are more capable of managing resources effectively and willing to accept technological breakthroughs. The study’s conclusions have significant policy ramifications specifically in the areas of finance, education and skills, and rural development that the Government should consider to increase farmer’s productivity and overcome various challenges while upholding national interests and ensuring the farming sector’s continued prosperity. To commercialize pineapple production and establish Bangladesh as a prominent production zone, more research and development are needed.